EFEKTIVITAS KAMPANYE NILAI KARAKTER POSITIF REMAJA DI MEDIA SOSIAL: STUDI KASUS KONTEN HUSAIN BASYAIBAN - Nabila Faizin; Saifullah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The high dependency of Generation Z adolescents on social media triggers character vulnerability, such as the normalization of digital moral decadence. Conversely, conventional Islamic Education delivery is often perceived as rigid. This study aims to analyze the characteristics of positive character value campaign content by Husain Basyaiban on TikTok, evaluate the moral value internalization process, and assess social media's effectiveness in shaping religious character. This study employed a descriptive qualitative approach with a case study design. Data were gathered through netnography on the TikTok account @kadamsidik00 and in-depth interviews with five adolescent informants in Pasuruan Regency selected via purposive sampling. Data analysis involved data reduction, display, and conclusion drawing, validated through triangulation. The results revealed three main findings: (1) Husain Basyaiban engineered content through eight thematic pillars, breaking abstract doctrines into small, practical, and aesthetic moral units (snackable micro-learning); (2) informants experienced real behavioral transformation, including improved commenting self-regulation, digital silence adoption, and a transition toward intrinsic worship motivation; and (3) horizontal storytelling effectively revitalized the principles of Tabayyun and Qoulan Sadida in cyberspace. Social media has successfully evolved from an entertainment platform into a "second school" that builds digital moral resilience.